ANALISIS PENGARUH PEMBERIAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. BANK SUMUT SYARIAH CABANG MARELAN DAN KOTA BANGUN - ian, Ian Alfian (Fakultas Ekonomi dan Bisnis Islam, 2019)
This study aims to determine the effect of providing motivation on employee performance at PT. Bank Sumut Syariah KCP Marelan and Kota Bangun. This research is a field research using a quantitative approach. The research results can be concluded that the provision of motivation has a significant effect on employee performance at PT. Bank Sumut Syariah KCP Marelan. This can be seen from the hypothesis test where the coefficient of determination (R2) shows 0.714 or 71.4%, meaning that the performance variable can be explained by the motivational variable by 71.4% while the remaining 28.6% is explained by other variables outside the research. And in the t test obtained tcount of 5,469. meaning tcount (5,469)> ttable (1,782) and Pvalue (0.00) <? (0.05), meaning that Ha is accepted and H0 is rejected. While the regression model formed states that motivation provides a significant effect on performance with a coefficient of 1,004 which means that if motivation is given as much as 1 time the performance will increase by 1,004.